Implementation of the Elementary School Administration Model in Increasing the Effectiveness of Learning Management - Hadi, Rusman; Mulyono, Ana (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to investigate the implementation of the elementary school administration model in increasing the effectiveness of learning management in the school environment. The administrative model implemented combines various strategies and approaches that focus on optimizing management, improving the quality of teaching, and strengthening relationships between all relevant stakeholders. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation and document analysis. Research respondents included principals, teachers, administrative staff, and students from several elementary schools that participated in the implementation of the administrative model. The research results show that the implementation of the elementary school administration model has contributed significantly to increasing the effectiveness of learning management. This model helps in increasing administrative efficiency, optimal use of resources, and more targeted learning planning. In addition, this administrative model encourages better collaboration between school stakeholders, including collaboration between school principals, teachers, administrative staff, and parents. This research concludes that the implementation of a holistic and collaboration-based elementary school administration model can provide great benefits in increasing the effectiveness of learning management. This model can be a reference for elementary schools in improving the quality and achievement of education and creating a more effective and competitive learning environment.